Alirocumab safety in people with and without diabetes mellitus: pooled data from 14 ODYSSEY trials. Issue 12 (9th October 2018) - Leiter, L. A.; Tinahones, F. J.; Karalis, D. G.; Bujas‐Bobanovic, M.; Letierce, A.; Mandel, J.; Samuel, R.; Jones, P. H.
Abstract: Aim: To evaluate the safety of the proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor alirocumab according to diabetes mellitus status. Methods: Safety data from 14 trials (8–104‐week durations) were analysed by treatment (alirocumab or placebo/ezetimibe control) and diabetes status (yes/no, defined by medical history). Adverse event data were assessed using descriptive statistics and Cox models. Results: Of the 5234 trial participants, 1554 (29.7%) had diabetes. Overall, treatment‐emergent adverse events were similar in the alirocumab and control groups, except for more frequent local injection site reactions with alirocumab. Fewer people with diabetes experienced local injection site reactions [alirocumab, 3.5%, control, 2.9%; hazard ratio 1.24 (95% CI 0.68–2.25)] than those without diabetes [alirocumab, 7.5%; control, 4.9%; hazard ratio 1.51 (95% CI 1.13–2.01)]. Those with diabetes reported a greater number of serious adverse events (alirocumab, 19.4%; control, 19.7%) than those without diabetes (alirocumab, 14.5%; control, 13.5%). In people with diabetes, major adverse cardiac events occurred in 2.7% of alirocumab‐treated people [control, 3.3%; hazard ratio 0.74 (95% CI 0.41–1.35)]; in those without diabetes, 1.8% of alirocumab‐treated people had major adverse cardiac events [control, 1.7%; hazard ratio 0.95 (95% CI 0.56–1.62)]. Overall, no increase in HbA1c or fasting plasma glucose vs control treatment groups was observed, regardless of diabetes status. Conclusion: This pooled analysis across 14 trials demonstrated similar safety for alirocumab vs control treatment, irrespective of diabetes status, except for more frequent local injection site reactions with alirocumab. People with diabetes reported fewer local injection site reactions than those without diabetes. What's new?: People with diabetes are at high cardiovascular risk and may require additional lipid‐lowering beyond statins. PCSK9 inhibitors provide additional LDL cholesterol reductions, but their safety has not been fully evaluated by diabetes status. Our pooled analysis of 14 phase 2/3 trials is the largest safety assessment of the PCSK9 inhibitor alirocumab in terms of study participant numbers ( n = 5234), comparing those with vs without diabetes at baseline over 8–104 weeks of treatment. Our findings show comparable safety for alirocumab vs control, irrespective of diabetes status, except for more frequent local injection site reactions with alirocumab; people with diabetes reported fewer local injection site reactions than those without. No clinically significant changes in glycaemic variables (fasting plasma glucose and HbA1c ) were observed in people with or without diabetes, regardless of treatment with alirocumab or control.